2015
DOI: 10.4028/www.scientific.net/kem.660.132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Storage Time on the Composition of the Olive and Sunflower Oils

Abstract: The effect of storage time on the composition of the olive and sunflower oils has been investigated. It were studied parameters like free fatty acids (FFA), anisidine value (AV), iodine value (IV), saponification number (SN) and identification of the molecular structure through FT-IR method. During storage (48 months) an increasing in the values of parameters FFA and AV took place that measures the oxidative degradation of oils. The oxidative stability of olive oil stored at room temperature was less than of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Results of present study indicate that the fatty acid profile of eggs could be altered by used WL in diets for laying hens. However, an improvement of omega-6 and omega-3 type fatty acids of eggs will result in a higher susceptibility to lipid oxidation and possibly a shorter shelf-life of stored eggs [39,40,41]. This could affect egg quality negatively, mainly due to a decrease in organoleptic and nutritional properties of eggs [42].…”
Section: Oxidative Stability Of Egg Yolkmentioning
confidence: 99%
“…Results of present study indicate that the fatty acid profile of eggs could be altered by used WL in diets for laying hens. However, an improvement of omega-6 and omega-3 type fatty acids of eggs will result in a higher susceptibility to lipid oxidation and possibly a shorter shelf-life of stored eggs [39,40,41]. This could affect egg quality negatively, mainly due to a decrease in organoleptic and nutritional properties of eggs [42].…”
Section: Oxidative Stability Of Egg Yolkmentioning
confidence: 99%
“…Apart from this, a regression function is considered to best approximate the set of the experimental points when the regression coefficient is as close as possible to the unity. 13,14 By processing the recorded experimental data, the Table Curve software gives 312 equations for the concentration, time and temperature as a relationship between the experimental results and the values calculated by the equations. After a careful selection, the determination coefficient values, the simplicity of the equations and the good arrangement of the experimental points on the response surface were taken into account for the equations in order to obtain all performance criteria.…”
Section: Tablementioning
confidence: 99%
“…Several studies dealing with the development of mathematic models that emphasize the performance of various catalysts in different processes revealed that the catalytical behavior is highlighted by the mathematical model developed using Table Curve software-that arranges the experimental data in a three-dimensional area. [11][12][13][14][15][16] This software is able to make a quick graphical and numerical analysis, providing the dependency relations between physical amounts that characterize the experimental data obtained, thus providing a mathematical model for the study. Furthermore, the software uses around 36.000 approximation procedures which have different equations so that it can establish the ideal approximation equation.…”
Section: Introduction *mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the growing demand for high-quality meat products, the challenges of the meat industry are to meet consumer expectations of delivering safe, high-quality meat [1,2]. Modern consumers expect to have access to soft and tender meat, with good taste, high nutritional value (rich in proteins, minerals, unsaturated fatty acids and vitamins), inducing positive influences on human health [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], safe for consumption, without pesticides, antibiotics and drug residues [19,20]. The consumers desire, as well, new types of food [21,22].…”
mentioning
confidence: 99%